Sex-Associated Differences in the Modulation of Vascular Risk in Patients with Asymptomatic Carotid Stenosis. Issue 4 (April 2015) - Buratti, Laura; Balestrini, Simona; Avitabile, Emma; Altamura, Claudia; Vernieri, Fabrizio; Viticchi, Giovanna; Falsetti, Lorenzo; Provinciali, Leandro; Silvestrini, Mauro
In this study, we aimed to identify determinants of the different sex-related stroke risk in subjects with asymptomatic internal carotid artery (ICA) stenosis. In all, 492 women (44.4%) and 617 men (55.6%), with unilateral 60% asymptomatic ICA stenosis, were prospectively evaluated with a median follow-up of 37 months (interquartile range, 26 to 43). Vascular risk profile, plaque characteristics, stenosis progression, and common carotid artery intima-media thickness were investigated. Outcome measure was the occurrence of ischemic stroke ipsilateral to ICA stenosis. Myocardial infarction, contralateral stroke and transient ischemic attack were considered as competing events. The incidence rate of ipsilateral stroke over the entire follow-up period was 0.16%: 0.09% (95% confidence interval (CI) 0.05 to 0.15) in women and 0.22% (95% CI 0.17 to 0.29) in men (log-rank test, P <0.001). Stenosis progression significantly influenced the risk of ipsilateral stroke in both men (subhazard ratio, SHR, 8.99) and women (SHR 4.89). Stenosis degree (71% to 90%, SHR 2.35; 91% to 99%, SHR 3.38) and irregular plaque surface (SHR 2.32) were relevant risk factors for ipsilateral stroke only in men. Our findings suggest that characteristics of the stenosis and plaque exert a different effect in modulating vascular risk in the two sexes. Understanding sex differences in cardiovascular disease could help to target sex-specific future therapies.